(untitled) (International Journal of Mathematics and Physics, 2020)
Transportation of highly viscous and high-curing oils through main pipelines requires significant energy costs. Thus, the task of choosing the cheapest pumping modes is very relevant. The article describes and proposes a solution to the oil flow problem in a pipeline using two methods: with preheating and using a Laval nozzle at the inlet of the pipeline. Mathematical models of the flow of highviscosity oil in the main oil pipeline for the two named pumping methods have been compiled. An algorithm has been developed for calculating temperature, viscosity and pressure along the length of the Uzen-Atyrau pipeline at various oil flow rates. The results of temperature and pressure distribution are analyzed and compared at different oil flow rates along the length of the pipeline for two pumping methods. It is shown that the use of cavitation improves the rheological properties of oil and can significantly reduce the cost of pumping. The research results can be used to predict the operation of main oil pipelines pumping oil both in a heated state and in isothermal mode with a Laval nozzle.